The Effect of Customer Experience, Shopping Motivation and Electronic Word of Mouth on Purchase Decisions Mediated by Online Trust (Study on Shopee E-commerce Users in Malang City) - Fian Arifiona Faradila; Heri Pratikto; Wening Patmi Rahayu (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
This study aims to analyze the mediation of trust on the influence of customer experience, shopping motivation, and electronic word of mouth (e-WOM) on purchase decisions among Shopee e-commerce users from generation Z in Malang City. This research approach is quantitative with descriptive and explanatory research methods. The data sample consisted of 174 respondents with a purposive sampling technique who had the criteria of being 17–29 years old, domiciled in Malang City, having the Shopee application, and having made a transaction in the last three months. Data processing was carried out using the Partial Least Square (PLS) method through SmartPLS 4 software. The results showed that customer experience, shopping motivation, and e-WOM had a significant effect on purchase decisions. In addition, trust was proven to significantly mediate the relationship between the three variables on purchase decisions. The R-Square value of 0.900 for trust and 0.905 for purchase decisions indicates that the research model has very strong explanatory power. These findings strengthen the relevance of the Technology Acceptance Model (TAM) and the Theory of Planned Behavior (TPB) theories in explaining the online purchasing behavior of Generation Z.